Selecting for Coupling Phase Recombination between Potyvirus Resitance and White Endosperm Colour in Maize Preferred by Farmers in Sub-Saharan Africa (SSA) - Bulegeya, Victoria B.; Jones, Mark W.; Muhamba, Tryphone G.; Das, Biswanath; Thomison, Peter R.; Francis, David M.; Redinbaugh, Margaret. G. (Afrika Focus, 2019)
Maize lethal necrosis (MLN) disease caused by a combined infection of Maize chlorotic mottle virus (MCMV) and any cereal infecting potyvirus is a threat to food security in Sub-Saharan Africa (SSA). Resistance to potyvirus has been extensively studied and Mdm1 gene for potyvirus resistance on chromosome 6 of maize is linked to Y1 gene for maize endosperm colour. This study is aimed at se- lecting for coupling-phase recombination of potyvirus resistance and white endosperm colour. White susceptible maize lines CML333 and CML277 were crossed with a yellow resistant line, Pa405, to produce F1 and F2 progenies. Progenies were screened using molecular markers to recover 22 white endosperm recombinants. 22 selections were advanced to F3 recombinant families, and 10 were as- sayed for their responses to Maize dwarf mosaic virus (MDMV) and Sugarcane mosaic virus (SCMV). Four families segregated for SCMV resistance, selection of homozygous recombinants within these families will provide lines appropriate for improving lines with resistance to SCMV and MLN resistance in SSA. KEY WORDS: MAIZE LETHAL NECROSIS (MLN), WHITE MAIZE, POTYVIRUS RESISTANCE, GENETIC RECOMBINATION, SUB-SAHARAN AFRICA.